Pengembangan Perangkat Pengajaran Mata Diklat Jaringan Komputer Dasar Berbasis Masalah - Ilham Tri Maulana; Fadil Firdian (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: Research objectives for developing learning devices. Development is carried out to help students master learning material and improve student learning outcomes. Development of teaching tools using the Model IDI (Institute Development Instructional). IDI development procedures include: analysis of learning needs, development, evaluation. Data analysis techniques using descriptive data analysis techniques to describe the validity, practicality, and effectiveness. The results of the study were an increase in student learning outcomes as well as valid, practical and effective learning tools. The conclusions of the study were an increase in the number of students who passed the basic computer network training course and recommended it for other courses. Abstrak: Tujuan penelitian untuk pengembangan perangkat pembelajaran. Pengembangan dilakukan untuk membantu siswa menguasai materi pembelajaran dan menaikkan hasil belajar siswa. Pengembangan perangkat pengajaran menggunakan Model IDI (Institute Development Instructional). Prosedur pengembangan IDI, meliputi analisis kebutuhan pembelajaran, pengembangan, evaluasi. Teknik analisis data menggunakan teknik analisis data deskriptif dengan mendeskripsikan validitas, praktikalitas, dan efektivitas. Hasil penelitian adanya peningkatan hasil belajar siswa serta perangkat pembelajaran yang valid, praktis, dan efektif. Simpulan dari penelitian terjadinya peningkatan jumlah siswa yang lulus mata diklat jaringan komputer dasar dan direkomendasikan untuk mata diklat lain.